If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8.75 + 9 = 12.5t + 12 Combine like terms: 8.75 + 9 = 17.75 17.75 = 12.5t + 12 Reorder the terms: 17.75 = 12 + 12.5t Solving 17.75 = 12 + 12.5t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-12.5t' to each side of the equation. 17.75 + -12.5t = 12 + 12.5t + -12.5t Combine like terms: 12.5t + -12.5t = 0.0 17.75 + -12.5t = 12 + 0.0 17.75 + -12.5t = 12 Add '-17.75' to each side of the equation. 17.75 + -17.75 + -12.5t = 12 + -17.75 Combine like terms: 17.75 + -17.75 = 0.00 0.00 + -12.5t = 12 + -17.75 -12.5t = 12 + -17.75 Combine like terms: 12 + -17.75 = -5.75 -12.5t = -5.75 Divide each side by '-12.5'. t = 0.46 Simplifying t = 0.46
| 3-(x-2)=4 | | 4r-6= | | 6/90=x/75 | | (3x+70)=x | | X+3-11x=x+5-7x-16 | | 5b+2(4b+3)=-59 | | 4x^4-x^3-3x^2+9x-10=0 | | 2x+75+52y+1=180 | | 3x=x+2+10 | | 15+47.45x=49.95x | | 2g+10=7g | | 6x+4x+3+7=5x+3+4x | | 9.5z=-161.5 | | 3x+12=-5x-60 | | (9x-15)^(1/2)=(7x-5)^(1/2) | | -3y+-y= | | 9.5z=161.5 | | 88-117=-6(-4y)-13(2y)+y | | y=6(x-4)2-7 | | 11x-0=16 | | -4n+9n-6=-58 | | 7y/6-1/6 | | -6x*3/4 | | 3/10m=25 | | 0.5n+0.5n+n=180 | | (3*x)+(3*8)=42 | | 2x-(x-2)=11 | | 2b-3+4b= | | 2(x+4)=2(-8-x-2x) | | 44-7x=20+5x | | 2z+3=4x+5 | | 8x-5=5m+7 |